Project-based learning on macromolecules using Ketapang natural resources: Fostering creativity and entrepreneurship - Titin Nurhayatin; Eli Rohaeti (Universitas Ahmad Dahlan, 2025)
The lack of variety of learning methods and teaching materials that are not contextualized causes low creative thinking skills and entrepreneurial attitudes of students in learning chemistry. This study aims to determine the differences in creative thinking skills and entrepreneurial attitudes of students simultaneously and respectively between groups using the Project-Based Learning (PjBL) model integrated with Ketapang natural resources and groups using a scientific approach. This research is a quasi-experiment with a pretest-posttest control group design, involving four XII classes that were randomly selected using cluster random sampling, with two classes (72 students) assigned to the experimental group receiving PjBL learning and two classes (70 students) to the control group receiving scientific approach learning. The instruments used were creative thinking skills test and entrepreneurial attitude questionnaire. Data were analyzed using descriptive statistics and MANOVA test. The results showed significant differences both simultaneously and per variable between the experimental and control classes. The integrated PjBL model made an effective contribution of 21.5% to both variables simultaneously, 13.6% to creative thinking skills, and 17.3% to entrepreneurial attitudes. This finding indicates that the project-based learning model associated with local potential is able to significantly improve students' thinking competencies and entrepreneurial attitudes.